Fostering now messages from research - Sinclair, Ian (Jessica Kingsley Publishers, 2005)
Fostering Now brings together authoritative research on foster care in the UK succinct overview of a wide range of research projects and highlights the main implications for policymakers and all professionals involved in the fostering process. Drawing on the varied experiences and views of foster children, social workers, foster carers and parents, this book looks at how placement outcomes are influenced by factors such as foster carers' parenting styles, contact with the child's own parents, and the child's gender, ethnicity, age and physical and emotional health.